(untitled) (Revista de História da UEG (REVHIST), 2024)
This article aims to analyze the construction of the funerary memory of the first Portuguese dynasty between the 12th and 14th centuries. For this reason, we investigated the election of burial places by the monarchs of the Portuguese House of Burgundy, of D. Afonso Henriques (1143 - 1185), the Founding King, to the last sovereign of the Afonsine dynasty, D. Fernando (1367 - 1383), emphasizing the formation of royal pantheons in the monasteries of Santa Cruz de Coimbra and Santa Maria de Alcobaça, in addition to the attempt to establish dynastic mausoleums in the Odivelas Monastery and Lisbon Cathedral. Initially, from the approach of the royal testaments, we analyze the transformations in conceptions about death in the period and their relationship with the choice of funeral monuments by kings. Subsequently, we propose to problematize the political meanings of the burial places of the Portuguese monarchy and their relations with the construction and evocation of royal memory, and their use in the affirmation of monarchical power in the Portuguese kingdom during the Late Middle Ages. Keywords: Royal Pantheons. Places of Burial. Death. Memory. Testaments.